Localized pleural metastasis without other organ metastases after nephrectomy for renal cell carcinoma. (2021) - Saito, Zenya; Hata, Kenichi; Nishioka, Saiko; Tamura, Kentaro; Tamura, Nobumasa; Yoshida, Masahiro; Kasa, Kentaro; Hirano, Jun; Masubuchi, Masataka; Kuwano, Kazuyoshi
Abstract: We present a case of a 69-year-old man who had localized pleural metastasis without other organ metastases after nephrectomy for right renal cell carcinoma (RCC). He complained of respiratory symptoms for more than two years after the operation and was confirmed to have right pleural effusion and multiple pleural masses on computed tomography (CT). There were no abnormal findings in the other organs, but the pleural mass gradually increased in size on CT. We suspected malignant tumors such as malignant pleural mesothelioma and synovial sarcoma in addition to RCC metastasis. Finally, we performed surgical resection of the pleural mass under general anesthesia, and we diagnosed pathologically as metastasis from RCC. Distant metastases of RCC are common in the lungs, bones, brain, and liver. To our knowledge, localized pleural metastases from RCC is rare.